The therapeutic potential of phytochemicals in morphine tolerance: targeting microglia-mediated neuroinflammation - Shi, Ruizhen; Jin, Tingting; Xu, Weilong; Liang, Yongxin (Frontiers in Pharmacology, 2025)
Morphine remains a first-line analgesic for both acute and chronic pain. However, its prolonged use often results in the development of tolerance, diminishing its analgesic efficacy and limiting its long-term clinical utility. Emerging evidence highlights the pivotal role of microglial activation in the central nervous system as a key contributor to morphine tolerance. Phytochemicals, natural metabolites derived from plants, have garnered attention for their multi-target mechanisms, low toxicity, and broad biological activities, positioning them as promising candidates for mitigating morphine tolerance. This review systematically explores the key receptors and signaling pathways involved in microglial activation during morphine tolerance, and elucidates how various phytochemicals modulate these pathways to attenuate tolerance. Furthermore, it discusses the translational challenges associated with phytochemical-based interventions and outlines future directions for their clinical application. The aim is to provide a theoretical framework to support translational research and the development of novel adjunct therapies for opioid analgesia.